Japan from shogun to superstate - Fewster, Stuart (St. Martin's Press, 1987)
The first half of this comprehensive textbook is a clear narrative account of Japanese history from the days of the shogun to the present. The second half is devoted to thematic chapters which trace developments in Japanese history; this context is then put to use in interpreting the current situation in Japan in the context of past events.